Presidential Neutrality and Position in the 2024 Presidential Election: A Constitutional Law and Comparative Law Perspective - weron murary (International Journal Labs, 2024)
In the event of the 2024 presidential election, the neutrality and position of the president play a key role in ensuring the continuity of democracy and justice. This article aims to investigate these issues from the perspective of constitutional law and comparative law. Through a normative juridical approach, this article explores the neutrality and position of the president in the 2024 general election from the perspective of constitutional law and comparative law. The data sources used come from primary and secondary sources. Based on the results of the analysis, it can be stated that the president as the people who have the right to vote and as the head of state who must prioritize neutrality towards the general election is prohibited from inviting others or the public to vote for one of the candidates. In addition, a legal comparison conducted with Malaysia, the Philippines, and South Korea found that the general elections conducted are almost the same as those conducted by Indonesia. Except Malaysia, because its form of government is a parliamentary constitutional monarchy. This means that executive power is held by the prime minister, who is the head of government and leads the cabinet. The Prime Minister is chosen from members of Parliament, who are members of the legislature elected by the people in general elections.